2019
DOI: 10.1186/s12935-019-0832-z
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin ligase CHIP modulates cellular behaviors of gastric cancer cells by regulating TRAF2

Abstract: Background CHIP is an E3 ubiquitin ligase that plays contrast roles in diverse human malignancies, depending on its targets. To date, the mechanisms underlying the function of CHIP in gastric cancer remains unclear. Here, we aim to further clarify the effects of CHIP on the development and progression of gastric cancer and explore its potential target. Methods Stably transfected CHIP-shRNA and TRAF2-shRNA AGS gastric cancer cell lines were established using Lipofectamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Gastric cancer (GC) is the fifth most prevalent cancer and the third most frequent cause of cancer-related deaths worldwide ( Bray et al, 2018 ), with almost 1,000,000 new cases and 800,000 deaths each year ( Torre et al, 2015 ; Bray et al, 2018 ). Owing to a lack of symptoms in the early stage, most patients with GC are usually diagnosed at an advanced stage ( Dai et al, 2019 ). Treatment options for patients at an advanced stage are limited, resulting in a relatively low 5-year survival rate (<20%) ( Katai et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer (GC) is the fifth most prevalent cancer and the third most frequent cause of cancer-related deaths worldwide ( Bray et al, 2018 ), with almost 1,000,000 new cases and 800,000 deaths each year ( Torre et al, 2015 ; Bray et al, 2018 ). Owing to a lack of symptoms in the early stage, most patients with GC are usually diagnosed at an advanced stage ( Dai et al, 2019 ). Treatment options for patients at an advanced stage are limited, resulting in a relatively low 5-year survival rate (<20%) ( Katai et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer (GC) is the third leading cause of cancer-related mortality and the fifth most frequently diagnosed malignancy worldwide ( 1 ), with almost 1,000,000 estimated new cases and 800,000 deaths each year ( 1 , 2 ). Due to the lack of early symptoms, most patients with GC are usually diagnosed at an advanced stage ( 3 ). Despite effective treatment, relapse and metastasis are common in advanced GC, causing a fairly low 5-year survival rate (<20%) ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we found that TRAF2 overexpression significantly rescued the migration ability in the presence of miR-671-5p (54.0 ± 7.0 vs. 21.0 ± 3.0, p = 0.00401). Although TRAF2 has less evidence in the GBM, there are several reported supporting that TRAF2 associated with migration of gastric cancer cells by regulating TRAF2 [ 24 ]. Overall, we concluded that MSI1 maintains EMT properties by inhibiting the miR-671-5p/TRAF2 axis.…”
Section: Resultsmentioning
confidence: 99%